A novel nonsense mutation of TGFBR1 in a fetus with untypical Loeys-Dietz syndrome 1 - Yang Yang; Wang Yan; Mao Aifen; Wang Hao (Elsevier, 2022)
Objective: We present a rare untypical Loeys-Dietz syndrome 1 case in prenatal setting and report a novel mutation in the TGFBR1 gene. Case report: A pregnant woman came for medical attention due to the fetal ultrasound anomaly. The fetus was found to have short long bones. Trio-based WES was applied to the family. A novel de novo nonsense mutation c.1237C > T was detected in the TGFBR1 gene. A diagnosis of Loeys-Dietz syndrome 1 (LDS1) was plausible, but the fetus did not demonstrate the characteristic phenotype of the syndrome. Conclusion: In prenatal setting, fetal phenotypes are difficult to be fully observed, putting stress on the utility of molecular techniques. LDS1 in fetuses could present untypical features such as skeletal dysplasia.